Antioxidant and anti-aging activities and structural elucidation of polysaccharides from Panax notoginseng root - Feng, Shiling; Cheng, Haoran (Process biochemistry, 2019)
Two novel polysaccharides, MRP5 and MRP5A, were obtained from the root of Panax notoginseng using column chromatography. Structure characterization suggested that MRP5A, with an average molecular weight of 11.38 × 104 Da, was composed of rhamnose (7.7%), arabinose (6.6%), glucose (69.8%) and galactose (15.9%). MRP5 had an average molecular weight of 9.16 × 104 Da and consisted of rhamnose (3.6%), arabinose (14.5%), glucose (51.2%) and galactose (29.7%). The results of methylation analysis and one-dimensional (1D) and two-dimensional (2D) nuclear magnetic resonance (NMR) spectra reveal that MRP5 contains repeating units of →3)-β-Glcp-(1→, →6)-β-Glcp-(1→, →3, 6)-Glcp-(1→, β-Glcp-(1→, →3)-β-Galp-(1→, →3, 6)-β-Galp-(1→, →3)-α-Rhap-(1→, →3)-α-Araf-(1→, and α-Araf-(1→ residues. MRP5 and MRP5A exhibited relatively low antioxidant abilities in vitro, but strongly protective effects against oxidative stress and lifespan extension effects in C. elegans. Overall, the present study indicated that MRP5 could be further investigated as a functional food for promoting healthspan.
Gesehen am 19.07.2019